ANALISIS PENELITIAN PERILAKU KONSUMEN - Hisam Asngari; Nadea Ananda Putri; Ni’matus Zahro (Jurnal Ilmiah Ekonomi Syariah, 2024)
This research aims to find out about consumer behavior in marketing, and the need for approaches to consumer behavior. Consumer behavior is the process that a business person goes through in finding a customer. Because the presence of a customer in a business can affect the growth and development of a business. Therefore, conducting a consumer behavior research analysis is very important in a company.